Kur’ân İlimlerinden el-Vücûh ve’n-Nazâir / A Quranic Science: al-Vucuuh va’n-nazair - Zavalsiz, Halit (Journal of History Culture and Art Research, 2015)
A Quranic Science: al-Vucuuh va’n-nazair Abstract Qur’an is a verbal and semantic miracle due to the fact that it is Allah’s word. If the mankind and the jinns were together to produce the like of this Qur'an, they could not produce the like thereof, even the shortest chapter of it and even if they helped one another. That is because Allah’s Word is the most beautiful one. Therefore, the sciences related to Quran is also the most valuable asset. Among the sciences of Quran is the science of al-vujuh and al-nazair. The science of al-vucuh deals with the words with multiple meanings whereas al-nazair is about the groups of words with same meanings but differing in written form and pronunciation. This science is about the linguistic explanation of Quran that every person engaged in commentaries of Quran (tafsir) should have a great knowledge about beside other sicences. In this article we studied the definition of this science, its importance, history and literature as well as its relations with other sciences. Kur’ân İlimlerinden el-Vücûh ve’n-Nazâir Öz Kur'ân'ı-Kerim lafzıyla manasıyla mucizedir. Çünkü o, Allah'ın kelamıdır. Bütün insanlar ve cinler, Kur'ân'ın benzerini getirmek üzere bir araya gelseler, birbirlerine yardım da etseler, onun kısa bir suresine nazîre yapamazlar. Kur'ân'ı-Kerîm kelamların en güzeli, Kur'ân ilimleri de ilimlerin en şereflisidir. Kur'ân ilimlerinden biri de, Vücûh ve Nazâir ilmidir. Vücûh, farklı anlamlara gelen kelimeleri; Nazâir ise, aynı anlama gelen kelimeleri ifade eder. Dolayısıyla Kur'ân'ı-Kerim'de birden çok manaya gelen (Vücûh) kelimeler olduğu gibi; aynı anlam için kullanılan (Nazâir) kelimeler de vardır ki, buna Kur'ân'ın lügavî tefsiri denir. Kur'ân tefsiri ile meşgul olan kişinin, diğer Kur'ân ilimleri yanında, bu ilmi de bilmesi gerekir. Aksi takdirde tefsir yapması caiz değildir. Bu makalede, kısaca bu ilmin tarifi, önemi, tarihçesi, diğer ilimlerle olan münasebeti ve konuyla ilgili eserlerin neler olduğu ortaya konulmuştur. علم الوجوه والنظائر الخلاصة إنّ القرآن الكريم معجز بلفظه و معناه، لأنه كلام الله. لئن اجتمعت الإنس والجن على أن يأتوا بمثل هذا القرآن لا يأتون بمثله، حتى بسورته القصيرة، ولو كان بعضهم لبعض ظهيرا. فإن كلام الله أحسن الكلام، و علومه أشرف العلوم. و من علوم القرآن علم الوجوه والنظائر. بينماالوجوه تفيد المعانى المختلفة فى الكلمة الواحدة، والنظائر تفيد الكلمات المختلفة فى المعنى الواحد. وعلم الوجوه والنظائر هو التفسير اللغوىّ للقرآن. فالذى يشتغل بتفسير القرآن يحتاج إلى معرفة هذا العلم _بجانب معرفة علوم القرآن الأخرى_ وفى مقالتنا هذه ذكرنا تعريف هذا العلم، و أهميته، و تاريخه، و المؤلفات التى تتعلق بهذا العلم، و مناسبته للعلوم الأخرى.